1666 Incidence and Risk Factors for post Cardiac Surgery Arrythmias in a Tertiary Paediatric Cardiac Referral Centre. (October 2012) - Adhvaryu, K; Johnson, R; Shetty, N
Abstract : Background and Aims: Arrhythmias in the immediate post- operative period are a significant cause of morbidity. Its incidence varies between 15–79% and depends on case mix of surgical patients and methods used to identify them. Our aim was to determine the incidence and risk factors for their occurrence in our regional cardiac referral centre. Methods: A retrospective study was conducted including all paediatric (newborn to 18 years) patients who underwent a surgical procedure requiring cardio-pulmonary bypass between September 2010 and August 2011. Patients were identified and data gathered from the cardiac databases, electronic patient records and typed operation notes. Patients were excluded if they had pre-operative arrhythmias or if the arrhythmias during surgery were so transient such that they only occurred in the operation theatre. Results: Of the 346 cases that met inclusion criteria, 15% developed arrhythmias of which half required intervention. Risk factors for arrhythmias included surgery involving the septum (21% vs 8% non-septal), male (17% vs 14%) and age less than one year (20% vs 9%). Those with arrhythmias had significantly longer bypass (160min vs 116min, p<0.05) and cross clamp times (101 min vs 77min, p<0.05). Transient rhythm problems that required intervention were sinus bradycardia, junctional rhythm, junctional ectopic tachycardia and supra ventricular tachycardia, whilst 43% of those with heart block required permanent pacing. Conclusion: Despite advances in surgical techniques arrhythmias after cardiac surgery were seen in a significant number (15%) of our patients although only a small proportion (< 1%) require long term interventions.